Geopolymer material compositely modified by nano boron chloride-polyimide fiber-meta-aramid fiber and preparation method of geopolymer material
Through the composite modification treatment of nanoborochloride-polyimide fiber-meta-aramid fiber, a stable mesh-like coupling structure is formed, which solves the problem of insufficient strength and toughness of the geopolymer material, and significantly improves the resistance to flexion and resistance. Pressure and crack resistance extend the service life of building materials and are suitable for high temperature environments.
Patent Information
- Application Number
- CN202411158418.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2024-12-31
AI Technical Summary
The existing poly materials have poor tensile resistance, poor deformation resistance, high brittleness and low toughness, which leads to cracks that are prone to occur under the influence of external environmental factors, affecting the durability and service life of the building structure.
Using nanoborochloride-polyimide fiber-meta-aramid fiber composite modified geopolymer material, nanoborochloride, polyimide fiber and metaaramid fiber are uniformly dispersed through surface pretreatment and uniform dispersion of nanoborochloride, polyimide fiber and metaaramid fiber. Form a stable mesh coupling structure to improve the mechanical properties and durability of the material.
It significantly improves the flexural strength, compressive strength, split tensile strength and drying and shrinkage properties of the geopolymer materials, extends the service life of building materials, and improves thermal stability and weather resistance, and is suitable for high-temperature environments.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of road engineering materials, and in particular to a geopolymer material compositely modified by nano boron chloride-polyimide fiber-meta-aramid fiber and a preparation method thereof. Background Art
[0002] Geopolymer material is an inorganic polymer geopolymer material with a three-dimensional network structure made of silicon-aluminum natural minerals or industrial solid waste as precursors and alkaline substances as activators. It is an environmentally friendly building material. Its main feature is that the raw materials are widely available, and silicon-aluminum raw materials can be extracted from industrial solid waste. However, due to some inevitable disadvantages of this type of material itself, such as poor tensile properties, poor deformation resistance, high brittleness, low toughness, and large crack width after cracking, cracks will continue to appear under the influence of external environmental factors, eventually leading to insufficient bearing capacity of the geopolymer, thereby affecting the durability and service life of the building structure. Therefore, it is particularly critical to develop a new modified geopolymer material to solve problems such as strength and toughness.
[0003] The information disclosed in this background technology section is only used to deepen the understanding of the background technology of the present disclosure, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0004] The present application provides a geopolymer material compositely modified by nano boron chloride-polyimide fiber-meta-aramid fiber and a preparation method thereof, aiming to solve the technical problem of insufficient building performance such as strength, toughness and durability of existing geopolymer materials.
[0005] According to one aspect of the present disclosure, a composite modified geopolymer material is provided, which is made of the following raw materials in parts by weight: 280 to 320 parts of sand, 70 to 90 parts of mineral powder, 15 to 25 parts of fly ash, 0.13 to 0.17 parts of nano boron chloride, 0.7 to 0.9 parts of polyimide fiber, 0.3 to 0.5 parts of meta-aramid fiber, 0.05 to 0.11 parts of coupling agent, and 20 parts of alkali activator.
[0006] In some embodiments of the present disclosure, the composite modified geopolymer material is made of the following raw materials in parts by weight: 300 parts of standard sand, 80 parts of mineral powder, 20 parts of fly ash, 0.15 parts of nano-boron chloride, 0.76 parts of polyimide fiber, 0.43 parts of meta-aramid fiber, 0.08 parts of coupling agent, and 20 parts of alkali activator.
[0007] In some embodiments of the present disclosure, the mineral powder is S95 grade slag powder.
[0008] In some embodiments of the present disclosure, the fly ash is Class I fly ash.
[0009] In some embodiments of the present disclosure, the coupling agent is a silane coupling agent (such as kh550, etc.).
[0010] In some embodiments of the present disclosure, the sand is at least one of river sand, standard sand, quartz sand, sea sand, and mixed sand.
[0011] In some embodiments of the present disclosure, the alkali activator is a water glass solution with a modulus of 1.2 to 1.5.
[0012] According to another aspect of the present disclosure, there is provided a method for preparing the above-mentioned geopolymer material, comprising the following steps: (1) Prepare the raw materials according to the above weight proportions; The nano boron chloride, coupling agent and water are mixed evenly in a mass ratio of 0.8-1.2:0.12-0.16:0.49-0.53, and the mixture is soaked for 1.5-2.5 hours, filtered and dried at 50-70° C. to obtain a nano boron chloride modifier; The polyimide fiber, the coupling agent and water are mixed evenly in a mass ratio of 0.8-1.2:0.09-0.13:0.32-0.36, soaked for 3.5-4.5 hours, and then dried at 50-70° C. to obtain a modified polyimide fiber; The meta-aramid fiber, the coupling agent and water are mixed uniformly in a mass ratio of 0.8-1.20:0.13-0.17:0.39-0.43, soaked for 5.5-6.5 hours, and then dried at 50-70° C. to obtain the modified meta-aramid fiber; (2) Dry-mix the nano-boron chloride modifier, modified polyimide fiber, modified meta-aramid fiber and sand for 1 to 5 minutes, then add the mineral powder and fly ash and dry-mix for 1 to 5 minutes, and finally add water and alkali activator and stir for 1 to 5 minutes to form a uniform slurry; (3) Inject the slurry into the oiled mold and cure the mold under standard conditions; (4) After 20 to 30 hours, demould and continue curing to the specified age.
[0013] In some embodiments of the present disclosure, in the step (4), after demoulding, the molded product is placed under standard curing conditions for curing.
[0014] One or more technical solutions provided in the embodiments of the present application have at least any of the following technical effects: 1. The composite modified geopolymer material provided in the present application is an environmentally friendly, non-toxic and non-corrosive composite geopolymer material with excellent mechanical properties and durability. Its flexural strength, compressive strength, splitting tensile strength, resistance to drying shrinkage and frost resistance are enhanced, thereby increasing the service life of the building material; its raw materials are non-toxic and harmless, and have a wide range of sources; the production process is pollution-free and low-priced, and has good economic benefits.
[0015] 2. In the composite modified geopolymer material of the present application, nano boron chloride, polyimide fiber and meta-aramid fiber are surface pretreated with a silane coupling agent (such as KH550, etc.) to enhance their dispersibility in the matrix, improve the interfacial bonding force between them and the matrix, and thus improve the performance of the composite material (increase mechanical properties, such as strength, toughness, hardness, etc. can be significantly improved; improve thermal stability and weather resistance, silane coupling agent can form a stable interface layer between nano boron chloride, polyimide fiber and meta-aramid fiber and the matrix to prevent the invasion of harmful substances such as moisture and oxygen, thereby improving the thermal stability and weather resistance of the composite material); the nano boron chloride, polyimide fiber and meta-aramid fiber after surface modification can form a stable network connection structure with raw materials such as mineral powder and fly ash inside the geopolymer material. This structure significantly enhances the mechanical strength and durability of the geopolymer material, while improving the locking force between aggregates, thereby greatly improving the toughness of the geopolymer material.
[0016] 3. Based on the good high-temperature chemical inertness, high thermal conductivity, high strength and elasticity of nano-boron chloride, it can improve the strength, hardness, wear resistance and crack resistance of geopolymer materials when combined with sand, fly ash, water glass or other matrix materials; nano-boron chloride as a reinforcing agent can significantly improve the strength, hardness and toughness of geopolymer materials, thereby enhancing the overall stability and durability of building structures; the chemical inertness and corrosion resistance of nano-boron chloride may help extend the service life of geopolymer materials and reduce material aging and damage caused by environmental factors (such as humidity, pH); in high-temperature environments, nano-boron chloride may help maintain the stability and structural integrity of geopolymer materials, making them suitable for special building scenarios that require high-temperature resistance (such as high-temperature industrial plants, nuclear power plants, etc.); polyimide fiber and meta-aramid fiber each have their own advantages in performance. The combination of the two can comprehensively improve the mechanical properties, heat resistance, flame retardancy and other comprehensive properties of geopolymer materials. The high strength and high-temperature resistance of polyimide fiber can complement the flame retardancy and chemical resistance of meta-aramid fiber, thereby meeting more complex and demanding application requirements.
[0017] 4. The preparation process of the composite modified geopolymer material provided in the present application is to first dry-mix the nano-boron chloride modifier, modified polyimide fiber, modified meta-aramid fiber and sand evenly, then add mineral powder and fly ash and dry-mix evenly, and finally add water and stir into a uniform slurry. This can ensure that the nano-boron chloride modifier and the fiber are evenly dispersed, the geopolymer material has better mechanical properties and durability, and the preparation process is simple. DETAILED DESCRIPTION
[0018] In order to better understand the technical solution of the present application, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0019] Unless otherwise specified, the raw materials involved in the following examples are all commercially available conventional raw materials; the preparation methods, detection methods and experimental methods involved are all conventional methods unless otherwise specified.
[0020] The composite modified geopolymer material in the following examples includes the following preparation steps: Prepare the raw materials according to the weight ratio of 300 parts of sand, 80 parts of mineral powder, 15-25 parts of fly ash, 0.13-0.17 parts of nano boron chloride, 0.7-0.9 parts of polyimide fiber, 0.3-0.5 parts of meta-aramid fiber, 0.05-0.11 parts of coupling agent and 20 parts of alkali activator; (1) Preparation of modifier: Nano boron chloride, coupling agent and water were mixed evenly in a mass ratio of 1:0.14:0.51 and soaked for 2 h, filtered and dried at 60°C to obtain a nano boron chloride modifier; The polyimide fiber, coupling agent and water were mixed evenly in a mass ratio of 1:0.11:0.34, soaked for 4 hours and then dried at 60°C to obtain modified polyimide fiber; The meta-aramid fiber, coupling agent and water were mixed uniformly in a mass ratio of 1:0.15:0.41, soaked for 6 hours and then dried at 60°C to obtain modified meta-aramid fiber; (2) Dry-mix the nano-boron chloride modifier, modified polyimide fiber, modified meta-aramid fiber and sand for 1 min, then add mineral powder and fly ash and dry-mix for 2 min, and finally add water and alkali activator and stir for 3 min to form a uniform slurry; (3) Inject the mineral powder slurry into the oil-coated mold. After the slurry fills the mold, smooth the surface and maintain the mold under standard conditions (temperature 18-22°C, relative humidity ≥90%). (4) Place the mold under standard conditions for about 24 hours and then remove it. After the mold is removed, place it in a constant temperature and humidity curing box under standard curing conditions for curing.
[0021] Example 1: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of river sand, 80 parts of mineral powder (S95 grade slag powder), 16 parts of fly ash (Grade I), 0.13 parts of nano boron chloride, 0.73 parts of polyimide fiber, 0.33 parts of meta-aramid fiber, 0.05 parts of coupling agent (silane coupling agent kh550), and 20 parts of alkali activator (water glass solution, modulus 1.4).
[0022] Example 2: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of standard sand, 80 parts of mineral powder (S95 grade slag powder), 18 parts of fly ash (Grade I), 0.14 parts of nano boron chloride, 0.76 parts of polyimide fiber, 0.36 parts of meta-aramid fiber, 0.06 parts of coupling agent (silane coupling agent kh550), and 20 parts of alkali activator (water glass solution, modulus 1.2).
[0023] Example 3: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of quartz sand, 80 parts of mineral powder (S95 grade slag powder), 20 parts of fly ash (Grade I), 0.15 parts of nano boron chloride, 0.79 parts of polyimide fiber, 0.39 parts of meta-aramid fiber, 0.07 parts of coupling agent (silane coupling agent kh550), and 20 parts of alkali activator (water glass solution, modulus 1.5).
[0024] Example 4: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of sea sand, 80 parts of mineral powder (S95 grade slag powder), 22 parts of fly ash (Grade I), 0.16 parts of nano boron chloride, 0.82 parts of polyimide fiber, 0.43 parts of meta-aramid fiber, 0.08 parts of coupling agent (silane coupling agent kh550), and 20 parts of alkali activator (water glass solution, modulus 1.3).
[0025] Example 5: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of mixed sand, 80 parts of mineral powder (S95 grade slag powder), 24 parts of fly ash (Grade I), 0.17 parts of nano boron chloride, 0.86 parts of polyimide fiber, 0.47 parts of meta-aramid fiber, 0.09 parts of coupling agent (silane coupling agent kh550), and 20 parts of alkali activator (water glass solution, modulus 1.4).
[0026] Comparative Example 1: A common geopolymer material is made from the following raw materials in parts by weight: 300 parts of river sand, 80 parts of mineral powder (S95 grade slag powder), 16 parts of fly ash (Grade I), and 20 parts of alkali activator (water glass solution, modulus 1.4).
[0027] The composite modified geopolymer materials in Examples 1-5 were subjected to mechanical property and durability tests, including flexural strength test, compressive strength test, splitting tensile strength test, drying shrinkage test and freeze-thaw cycle test, to test the performance of the composite modified geopolymer materials of the present invention, and compared with the unmodified geopolymer materials for analysis. The test results are shown in Table 1.
[0028] Table 1 Mechanical properties and durability test indicators of different geopolymer materials .
[0029] As can be seen from Table 1, the 28-day flexural strength of the composite modified geopolymer material is greater than that of the unmodified geopolymer material (Comparative Example 1), indicating that the toughness of the composite modified geopolymer material is stronger than that of the unmodified geopolymer material; the 28-day compressive strength of the composite modified geopolymer material is greater than that of the unmodified geopolymer material, indicating that the hardness and compressive resistance of the composite modified geopolymer material are stronger than those of the unmodified geopolymer material; the 28-day splitting tensile strength of the composite modified geopolymer material is greater than that of the unmodified geopolymer material, indicating that the crack resistance of the composite modified geopolymer material is stronger than that of the unmodified geopolymer material; the 90-day shrinkage rate of the composite modified geopolymer material is less than that of the unmodified geopolymer material, indicating that the volume stability and crack resistance of the composite modified geopolymer material are stronger than those of the unmodified geopolymer material; the 100-time mass loss rate of the composite modified geopolymer material is less than that of the unmodified geopolymer material, indicating that the extreme temperature damage resistance and durability of the composite modified geopolymer material are stronger than those of the unmodified geopolymer material.
[0030] The composite modified geopolymer material of the present application meets the relevant requirements of GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)", JC / T 603-2004 "Test method for shrinkage of cement mortar", and JGJ / T 70-2009 "Test method for basic properties of building mortar" standards, and its flexural strength, compressive strength and other indicators are significantly higher than those of the unmodified geopolymer material, indicating that the performance of the geopolymer material of the present invention is superior.
[0031] The present application has been described in detail above in conjunction with the embodiments; however, those skilled in the art will appreciate that, without departing from the inventive concept, the specific parameters in the above embodiments may be changed, or the relevant materials and method steps may be replaced by equivalents, thereby forming multiple specific embodiments, which are all within the common variation range of the present application and will not be described in detail one by one here.
Claims
1. A geopolymer material compositely modified by nano boron chloride-polyimide fiber-meta-aramid fiber, characterized in that: Made from the following raw materials in parts by weight: 280-320 parts of sand, 70-90 parts of mineral powder, 15-25 parts of fly ash, 0.13-0.17 parts of nano boron chloride, 0.7-0.9 parts of polyimide fiber, 0.3-0.5 parts of meta-aramid fiber, 0.05-0.11 parts of coupling agent, and 20 parts of alkali activator.
2. The geopolymer material according to claim 1, characterized in that: Made from the following raw materials in parts by weight: 300 parts of sand, 80 parts of mineral powder, 20 parts of fly ash, 0.15 parts of nano boron chloride, 0.76 parts of polyimide fiber, 0.43 parts of meta-aramid fiber, 0.08 parts of coupling agent, and 20 parts of alkali activator.
3. The geopolymer material according to claim 1, characterized in that: The sand is at least one of river sand, standard sand, quartz sand, sea sand and mixed sand.
4. The geopolymer material according to claim 1, characterized in that: The mineral powder is S95 grade slag powder.
5. The geopolymer material according to claim 1, characterized in that: The fly ash is Class I fly ash.
6. The geopolymer material according to claim 1, characterized in that: The coupling agent is a silane coupling agent.
7. The geopolymer material according to claim 1, characterized in that: The alkaline activator is a water glass solution with a modulus of 1.2 to 1.
5.
8. A method for preparing the geopolymer material according to claim 1, characterized in that: The steps include: (1) preparing the raw materials according to the weight proportions as described in claim 1; The nano boron chloride, coupling agent and water are mixed evenly in a mass ratio of 0.8-1.2:0.12-0.16:0.49-0.53, and the mixture is soaked for 1.5-2.5 hours, filtered and dried at 50-70° C. to obtain a nano boron chloride modifier; The polyimide fiber, the coupling agent and water are mixed evenly in a mass ratio of 0.8-1.2:0.09-0.13:0.32-0.36, soaked for 3.5-4.5 hours, and then dried at 50-70° C. to obtain a modified polyimide fiber; The meta-aramid fiber, the coupling agent and water are mixed uniformly in a mass ratio of 0.8-1.20:0.13-0.17:0.39-0.43, soaked for 5.5-6.5 hours, and then dried at 50-70° C. to obtain the modified meta-aramid fiber; (2) Dry-mix the nano-boron chloride modifier, modified polyimide fiber, modified meta-aramid fiber and sand for 1 to 5 minutes, then add the mineral powder and fly ash and dry-mix for 1 to 5 minutes, and finally add water and alkali activator and stir for 1 to 5 minutes to form a uniform slurry; (3) Inject the slurry into the oiled mold and cure the mold under standard conditions; (4) After 20 to 30 hours, demould and continue curing to the specified age.
9. The preparation method according to claim 8, characterized in that: In the step (4), after demoulding, the molded product is placed under standard curing conditions for curing.
